Cuando la vida no es increíble: La gran aventura LEGO como una obra dirigida al público adulto - Saravia Vargas, Juan Carlos (San José: Universidad de Costa Rica, Escuela de Estudios Generales, 2023)
The LEGO Movie (2014) was advertised as a children’s film because it was based on the memorable LEGO construction blocks and the figures in the toy line, which were animated with CGI. However, an analysis of the humor resources and the themes of the movie reveals that the main message of the film is directed to adults. This article will look at the black humor and slapstick comedy, the references to the corporative world, the dystopian vision of society, and the story within the story in The LEGO Movie, all fundamental film elements that appeal to adults and not minor viewers.